KAUM AL HADRAMAUT DAN PENYEBARAN ISLAM DI KALIMANTAN BARAT - Patmawati Patmawati; Fitri Kusumayanti (The Institute for Research and Community Service (LP2M) of Pontianak State Institute of Islamic Studies (IAIN Pontianak), 2023)
The article aims to describe the diaspora of the Hadramauts in the spread of Islam in West Kalimantan. The research uses a qualitative approach with data collection through observation, interviews, and documentation. The research results show: First, the diaspora of the al-Hadramaut people was based on political, economic, and da'wah factors. Especially since the death of Ali bin Abi Thalib as the last caliph of Khulafaur Rasyidin, especially the political pressure of Bani Umayyah, following Bani Abbasiyah on the political rights of Bani Hasyim. Making Bani Hasyim leave Hijas for Yaman as a trader and preacher in the West Kalimantan region. Second, preaching through cultural and structural approaches that created the birth of various Islamic kingdoms in Sumatra, Java, Sulawesi, Kalimantan, Maluku and others. Third, his position as a formal and informal leader, as well as being attached to the power of following to give birth to the Kubu kingdom and the Pontianak Kingdom.